Implementasi Algoritma Apriori Dalam Menentukan Penyusunan Buku di Perpustakaan - Peter Gelu, Leonard; Chrisinta, Debora; Eduardo Simarmata, Justin (Institut Teknologi Garut, 2025)
University libraries play an important role in supporting the learning and research processes. However, book borrowing transaction data is often not optimally utilized to understand user needs. This study aims to identify book borrowing patterns at the University of Timor Library in order to find associations between book types that can be used for reading recommendations and collection management. The method used is association rule mining with the Apriori algorithm on book borrowing transaction data for the 2023–2024 period. The analysis results show strong association patterns between several book titles, particularly in the fields of finance and taxation, such as “Financial Statement Analysis and Its Application,” “Value Added Tax,” and